Pengaruh Ukuran Bank, Fungsi Intermediasi Bank dan Variabel Moneter Terhadap Pertumbuhan Ekonomi Indonesia Periode 2015-2020 - Maharani Maharani; Tiara Nirmala (Goodwood Publishing, 2022)
This study aims to determine the effect of bank size, bank intermediation function and monetary variables on Indonesia's economic growth in the long and short term. This type of research is quantitative research using secondary data with quarterly data format for the period 2015 – 2020. This research uses the Error Correction Model (ECM) method. The variables used in this research are bank total assets, loan to deposit ratio (LDR), Bank Indonesia's Interest Rate and inflation. The results of this study indicate that based on the results of the Ordinary Least Square (OLS) estimation, bank total assets and the reference interest rate have a significant negative effect on Indonesia's economic growth in the long term and the loan to deposit ratio and inflation variables have a significant positive effect on Indonesia's economic growth in the long term. Based on the results of the cointegration test, it has been stationary at the level, so that cointegration occurs between variables. Based on the results of the short-term ECM test, the loan to deposit ratio (LDR) variable and inflation have a significant positive effect on Indonesia's economic growth.